Comment on "Design of PID controllers for interval plants with time delay". (August 2016) - Firouzbahrami, Majid; Nobakhti, Amin
Abstract : Highlights: We study results presented in a recently published paper in Journal of Process Control titled "Design of PID controllers for interval plants with time delay". We propose an explicit counterexample for all the presented results. The counterexample can also be used to refute some results in the literature. Source of the inaccuracy is discussed in the paper. Abstract: In[1] three theorems are presented which relate to the problem of stabilizing PID controller design for interval time-delay plants. We present a counterexample for these results.